Soret and dufour effects on unsteady boundary layer flow and heat transfer of nanofluid over a stretching/shrinking sheet: a stability analysis - Dzulkifli, Nor Fadhilah; Bachok @ Lati, Norfifah; Pop, Ioan; Yacob, Nor Azizah; Md. Arifin, Norihan; Rosali, Haliza (OMICS International, 2017)
The effects of Soret and Dufour parameters on the boundary layer flow in nanofluid over stretching/ shrinking with time dependent is studied using Buongiorno model. The system of partial differential equations is transformed to the system of ordinary differential equations by applying similarity transformation. The results are obtained numerically using bvp4c in Matlab. The reduced skin friction coefficient reduced Nusselt number, velocity, temperature and concentration profiles are shown graphically with different values of Soret effect, Dufour effect, mass flux parameter, unsteadiness parameter, thermophoresis as well as Brownian motion parameter where the dual solutions are obtained. The unsteadiness parameter and mass flux parameter expand the range of solution for stretching/ shrinking parameter. Meanwhile, the Soret and Dufour parameters are found to affect the heat transfer rate at the surface. In order to determine the stability of the solutions, stability analysis is performed.